Allelopathic effect of Cyperus rotundus L. on the germination of bioindicators and in the initial growth of corn (Zea mays) (Research, Society and Development, 2024)
The invasive plant sedge (Cyperus rotundus L.) is quite aggressive, and difficult to control worldwide, causing losses in agriculture. The objective of this work was to identify possible allelopathic effects of aqueous extracts of dried nutsedge leaves on seed germination of chicory and cucumber bioindicators. The seeds were placed in petri dishes, lined with filter paper, with five treatments (0%, 2,5%, 5,0%, 7,5% and 10%), with four replications. The effect of sedge powder on the initial growth and root and rhizome anatomy of corn in a greenhouse was also tested, using three treatments: control (T1), (T2) with 5,57 g of sedge powder and (T3) with 11,15 g of sedge powder. The results were submitted to ANOVA and the means compared by Tukey at 5% probability. The extract showed negative allelopathic potential in chicory. For cucumber, there was a shorter root length in treatments with extract. In the initial growth of maize, the extract stimuled the percentage of maize emergence. In the anatomy of corn roots, there was formation of aerenchyma and accumulation of allelochemicals in the epidermis and cortex. In the rhizome (stem) there were no changes.